Unpacking the ESG ratings: Does one size fit all? - Monica Billio; Aoife Claire Fitzpatrick; Carmelo Latino; Loriana Pelizzon (Leibniz Institute for Financial Research SAFE, 2024)
In this study, we unpack the ESG ratings of four prominent agencies in Europe and find that (i) each single E, S, G pillar explains the overall ESG score differently, (ii) there is a low co-movement between the three E, S, G pillars and (iii) there are specific ESG Key Performance Indicators (KPIs) that are driving these ratings more than others. We argue that such discrepancies might mislead firms about their actual ESG status, potentially leading to cherry-picking areas for improvement, thus raising questions about the accuracy and effectiveness of ESG evaluations in both explaining sustainability and driving capital toward sustainable companies.
Keywords: M14; G24; G11; 330; ESG Investing; ESG ratings; Asset Allocation; Portfolio Management; Sustainable Finance